Islamic Education Internalisasi Nilai Kekhalifahan dalam Pengelolaan Lingkungan: Perspektif Teologi Islam terhadap Keadilan Ekologis: Internalization of the Values of Khalīfah (Stewardship) in Environmental Management: An Islamic Theological Perspective on Ecological Justice - hani, Luthfia Hanifatus Saiyidah; Imam Syafi’i; Baharudin; Ali Murtadho (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The global environmental crisis, characterized by global warming, deforestation, and ecosystem degradation, has raised demands for moral and spiritual responsibility in maintaining ecological balance. In Islamic teachings, humankind is designated as khalifah fil-ardh (vicegerent on earth), entrusted with the duty to preserve God’s creation and prevent environmental destruction (fasād). This study was conducted to analyze the human responsibility as khalifah in managing natural resources from an Islamic theological perspective, to identify contemporary challenges that hinder its implementation, and to formulate practical operational strategies. A qualitative-descriptive approach was employed through literature analysis of Islamic sources and previous studies related to environmental ethics. The findings indicate that the values of khalifah provide a normative framework for ecological justice; however, their implementation remains weak due to the dominance of economic interests, weak regulatory enforcement, and the lack of ecological awareness among communities. Therefore, the strengthening of khalifah values needs to be carried out through sustainable public policies, spiritually based environmental education, and active community participation. It is thus emphasized that the theocentric paradigm in Islam can serve as an ethical foundation for sustainable development and global environmental preservation.